Sociodemographic differences in motives for food selection: results from the LoCard cross-sectional survey - Hanna Konttinen; Otto Halmesvaara; Mikael Fogelholm; Hannu Saarijärvi; Jaakko Nevalainen; Maijaliisa Erkkola (BMC, 2021)
Abstract Background Although sociodemographic differences in dietary intake have been widely studied, the up-to-date evidence on the corresponding variations in motives for food selection is limited. We investigated how sociodemographic characteristics and special diets in households are associated with the relative importance of various food motives. Methods Participants were members of the S Group loyalty card program across Finland who consented to release their grocery purchase data to be used for research purposes and responded to a web-based questionnaire in 2018 (LoCard study). Self-reported information on sociodemographic factors (age, gender, marital status, living situation, education, household income), special diets in household and food motives (Food Choice Questionnaire) were utilized in the present analyses (N = 10,795). Age- and gender-adjusted linear models were performed separately for each sociodemographic predictor and motive dimension (derived by factor analysis) outcome. The importance of each sociodemographic predictor was evaluated based on an increase in R 2 value after adding the predictor to the age- and gender-adjusted model. Results Age emerged as a central determinant of food motives with the following strongest associations: young adults emphasized convenience (∆R 2 = 0.09, P < 0.001) and mood control (∆R 2 = 0.05, P < 0.001) motives more than middle-aged and older adults. The relative importance of cheapness decreased with increasing socioeconomic position (SEP) (∆R 2 = 0.08, P < 0.001 for income and ∆R 2 = 0.04, P < 0.001 for education). However, the price item ("is good value for money") depicting the concept of worth did not distinguish between SEP categories. Considerations related to familiarity of food were more salient to men (∆R 2 = 0.02, P < 0.001) and those with lower SEP (∆R 2 = 0.03, P < 0.001 for education and ∆R 2 = 0.01, P < 0.001 for income). Respondents living in households with a vegetarian, red-meat-free, gluten-free or other type of special diet rated ethical concern as relatively more important than households with no special diets (∆R 2 = 0.02, P < 0.001). Conclusions We observed sociodemographic differences in a range of food motives that might act as barriers or drivers for adopting diets that benefit human and planetary health. Interventions aiming to narrow SEP and gender disparities in dietary intake should employ strategies that take into account higher priority of familiarity and price in daily food selection in lower-SEP individuals and males.